Molecular Diagnosis of Lumpy Skin Disease Outbreak in Cattle of Bidar, Karnataka - Shilpa,; Halmandge, Sandeep; Kasaralikar, Vivek; Ravindra , B G; Mallinath , K C; Rajendrakumar , T (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Lumpy skin disease is an infectious, arthropod born disease caused by lumpy skin disease virus (LSDV) belongs to genera Capripox virus family poxviridae. In the recent past, Karnataka experiencing several outbreaks of LSD with severe economic loss. The disease characterized by pyrexia, enlarged superficial lymph nodes, nasal discharge, watery eyes and characteristic generalized, firm, flat topped papules and nodules of 0.5–5.0 cm size all over the body causing lameness, severe emaciation, conjunctivitis, keratitis and corneal opacity. Based on clinical signs the disease is diagnosed and confirmed by PCR and phylogenetic analysis. Blood and tissue samples were collected from 26 animals among the total 226 suspected cases of LSD with varying degree of clinical signs and nodular lesions. Conventional capripox generic PCR detected 65.38 % of   P32 gene and F gene in skin biopsy samples. Phylogenetic analysis of P32 gene showed that the isolates from this study showed the similarity with other Indian isolates.
Keywords: Capripox virus; Lumpy skin disease; Phylogenetic analysis